Nutrient management on leaf area index of potato-mungbean- T. aman rice cropping pattern (Bangladesh Journal of Agricultural Research, 2015)
A field experiment was conducted at Regional Wheat Research Centre of the Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh for 2 consecutive years during 2006-07 and 2007-08. The objective was to find out the optimum nutrient management practice on leaf area index of each component crop of potato-mungbean-T. Aman rice cropping pattern. Twelve nutrient management treatments were tested in RCBD with 3 replications. Treatments combination based on cropping pattern were T1=HYG (0-198-44- 194-24-6-1.2 for potato; 0-24-40-48-24-3-1.2 for mungbean ; 0-80-16-44-12-2-0 for T.Aman rice ), T2=MYG (0-140-34-138-18-4.5-0.9 for potato; 0-20-36-40- 20-2-1 for mungbean ; 0-56-12-32-8-1.5-0 for T.Aman rice), T3=IPNS (10000- 168-38-170-18-6-1.2 for potato ; 5000-9-37-36-21-3-1.2 for mungbean ; 5000- 65-13-32-9-2-0 for T.Aman rice), T4=STB (0-171-40-164-22-5-1 for potato; 0- 20-36-40-22-2-1 for mungbean ; 0-68-15-37-11-2-0 for T.Aman rice), T5=FP (0- 97-16-91-0-0-0 for potato ; 0-6-5-4-0-0-0 for mungbean ; 0-39-37-12-0-0-0 for T.Aman rice), T6=CON (0-0-0-0-0-0-0 for potato, mungbean and T.Aman rice) kg/ha CDNPKSZnB, T7=HYG+CRI, T8=MYG+CRI, T9=IPNS+CRI, T10=STB+CRI, T11=FP+CRI, T12=CON+CRI for potato-mungbean T.Aman rice cropping pattern, respectively. Average of two years data showed that HYG+CRI treatment gave maximum LAI followed by HYG, IPNS+CRI, IPNS, STB+CRI, and STB treatments at 60 days after planting (DAP) for potato, at 50 days after sowing (DAS) for mungbean, at 60 days after transplanting (DAT) for T.Aman rice, respectively. For potato, there was a significant (p?0.01) and positive linear relation between the LAI at 60 DAP and the tuber yield. While there was a significant (p?0.01) and positive linear relationship between the LAI at 50 DAS and seed yield of mungbean. In case of T.Aman rice, there was a significant (p?0.05) as well as positive linear relationship between the LAI at 60 DAT and the grain yield of rice. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21994 Bangladesh J. Agril. Res. 39(3): 515-527, September 2014